1980
DOI: 10.1103/physrevd.22.2793
|View full text |Cite
|
Sign up to set email alerts
|

Central collisions between heavy nuclei at extremely high energies: The fragmentation region

Abstract: We discuss central collisions between heavy nuclei of equal baryon number at extremely high energies. We make a crude estimation of the energy deposited in the fragmentation regions of the nuclei. We argue that the fragmentation-region fragments thermalize, and two hot fireballs are formcd. These fireballs would have rapidities close to the rapidities of the original nuclei. We discuss the possible formation of hot, dense quark plasmas in the fireballs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 59 publications
1
139
1
Order By: Relevance
“…Of course we were looking at central rapidity i.e. CM system, quite different from the work of Anishetty et al [133]. Hagedorn explains the time line of our and related work in his 1984 review [13].…”
Section: How Did the Name Qgp Come Into Use?mentioning
confidence: 99%
See 2 more Smart Citations
“…Of course we were looking at central rapidity i.e. CM system, quite different from the work of Anishetty et al [133]. Hagedorn explains the time line of our and related work in his 1984 review [13].…”
Section: How Did the Name Qgp Come Into Use?mentioning
confidence: 99%
“…It is regrettable that once Chapline-Kerman ran into resistance they did not pursue the publication, and/or further development of their idea; instead, a) A year later, Kerman (working with Chin who gave him the credit for the QGP-RHI connection idea in his paper), presents strangelets [131], cold drops of quark matter containing a large strangeness content. b) And a few years later, Chapline [132] gives credit for the quark-matter connection to RHI collisions both to Chapline-Kerman [125] work, and the work of Anishetty, Koehler, and McLerran of 1980 [133]. Anishetty et al claim in their abstract .…”
Section: How Did the Name Qgp Come Into Use?mentioning
confidence: 99%
See 1 more Smart Citation
“…The leading consideration was to achieve a "clean" central rapidity region, i.e., with small net baryon density. Experiments at the ISR indicated that the projectile and target fragmentation regions in pp collisions were two units of rapidity wide; nuclear effects were expected possibly to double this number [24]. Thus a lower bound on the energy would be 50 GeV/A per beam.…”
Section: The Beginnings Of Rhicmentioning
confidence: 99%
“…Since the projectile is assumed highly relativistic (c => 1), the position where the particle is emitted is z(y) - Beyond that point, nuclei pass through each other although they do get compressed to ~(4-5)p Q in the porcess. 48,44 The energy density, in contrast to the baryon density.continues to increase with energy as we shall see in the next section.…”
Section: Stopping Power and Longitudinal Growthmentioning
confidence: 93%